Melatonin improves the seed filling rate and endogenous hormonal mechanism in grains of summer maize. Issue 2 (18th January 2021) - Ahmad, Shakeel; Kamran, Muhammad; Zhou, Xunbo; Ahmad, Irshad; Meng, Xiangping; Javed, Tehseen; Iqbal, Anas; Wang, Guoyun; Su, Wennan; Wu, Xiaorong; Ahmad, Parvaiz; Han, Qingfang
Abstract: The unpredictable precipitation and water deficit conditions in semiarid regions significantly reduce the yield of summer maize. The exogenous application of plant growth regulators can be used as a strategy to enhance plant stress tolerance and improve the growth and yield of maize under semiarid conditions. Here, we studied the protective role of melatonin application on maize yield using grain filling rate and hormonal crosstalk in maize grains. In the first field experiment, seeds were soaked with melatonin at a concentration of 0 (SM0 ), 25 (SM1 ), 50 (SM2 ), and 75 μM (SM3 ) μM. In contrast, in the second experiment, melatonin was applied on the foliage at the ninth leaf stage at a concentration of 0 (FM0 ), 25 (FM1 ), 50 (FM2 ), and 75 (FM3 ) μM. Our findings showed that melatonin treatments as seed soaking significantly increased single seed weight, seed filling rate in superior, medium and inferior seeds by regulating the hormone levels compared to foliar application. Application of melatonin significantly increased the zeatin+zeatin riboside (Z+ZR), indole‐3‐acetic acid (IAA), and gibberellic acid (GA) contents. However, it significantly inhibited the contents of abscisic acid (ABA) during the seed filling period. The content of Z+ZR, IAA, and GA was positively correlated with the maximum seed filling rate, seed weight, and mean filling rate in middle, superior and lower seeds, while the ABA was negatively correlated. The ABA content in inferior seeds was positively correlated with the maximum and mean seed filling rate. In semiarid regions, melatonin treatment of SM2 and FM2 significantly increased the dry matter per plant, 100‐grain weight, seed filling rate, IAA, Z+ZR, GA contents, ear characteristics, and maize yield.